Transport routes design to improve operational efficiency at Mabara Contratistas Generales S.C.R.L. - Fernández-Hernández, Alexis Fabián; Rivasplata-Sanchez, Absalon; Baca-Lopez, Marcos Gregorio (LACCEI, 2025)
In the electricity sector, efficiency in the management of transportation routes is essential to reduce costs and improve productivity. MABARA Contratistas Generales S.C.R.L., a provider of electrical services in the Lambayeque region of Peru, faces inefficiencies in route planning, which generates high operating costs and long travel times. The purpose of this study is to optimize the design of transportation routes to improve the company's operational efficiency. For this purpose, four optimization approaches were implemented and compared: sweep heuristics, savings heuristics, clustering heuristics and genetic algorithm, all programmed in Python. The evaluation was performed based on key indicators such as fuel costs, travel times, distance traveled, and operational efficiency. The results indicate that the savings heuristic is the most efficient method, achieving a 27.1% reduction in fuel costs, a 33% decrease in travel times and an 18.52% increase in operational efficiency. Therefore, it is concluded that the implementation of this method, together with personnel training and geographic information systems, significantly optimizes the company's logistics operations.